Development of real-time pcr technology for the rapid detection of mycobacterium tuberculosis resistance to reserve antituberculosis drugs: fluoroquinolones, amikacin, and capreomycin - Yu. S. Alyapkina; Ya. I. Alekseev; D. A. Varlamov; L. V. Domotenko; L. K. Shipina; M. A. Vladimirsky (Туберкулез и болезни лёгких)
Based on a real-time PCR technology using an original-design system of allele-specific, fluorophore-labelled primers complementary to the sequence of a fluorescence quencher, the authors developed a method and test system prototypes for the rapid determination of Mycobacterium tuberculosis (MBT) DNA mutations responsible for resistance to reserve anti-TB drugs, such as fluoroquinolones, amikacin, and capreomycin.To study drug susceptibility, an Amplitube-MDR-RV molecular genetic test system was used to investigate sputum smears from 68 patients with destructive pulmonary tuberculosis who had been long treated with first- and second-line drugs (53 patients). These patients excreted multidrug-resistant MBT in 51 (75%) cases. All obtained MBT DNA samples were also examined for resistance to fluoroquinolones, amikacin, and capreomycin, by employing both the developed method and prototype reagent kits and by conventional culture methods. Molecular genetic analysis established that the study had a sensitivity of 90% and a specificity of 96%.